2008
DOI: 10.1002/rra.1170
|View full text |Cite
|
Sign up to set email alerts
|

Role of abiotic and biotic factors in structuring the metazoan plankton community in a lowland river

Abstract: Water and quantitative zooplankton samples were collected at approximately monthly intervals from June 2000 to June 2002 in the middle section of the Po River (Northern Italy). Highly variable hydrological conditions were observed in the 2 years, with river flow varying approximately between 400 and 9300 m 3 s À1 . Dissolved inorganic nitrogen (DIN) usually decreased at higher river discharges. Autotrophic production was limited by phosphorus availability during the growing period (May-October); no significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
33
1
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 58 publications
(57 reference statements)
8
33
1
2
Order By: Relevance
“…Many studies in stream ecosystems have showed seasonality as the main variable correlated with higher values of algal biomass, chlorophyll-a and species richness (Rodrigues et al 2007, Borges and Train 2009, Rossetti et al 2009, Tavernini et al 2011. In the present study, the higher rainfall recorded during the summer might be the explanation for the higher biomass and diversity observed in the studied streams.…”
Section: Discussionsupporting
confidence: 59%
“…Many studies in stream ecosystems have showed seasonality as the main variable correlated with higher values of algal biomass, chlorophyll-a and species richness (Rodrigues et al 2007, Borges and Train 2009, Rossetti et al 2009, Tavernini et al 2011. In the present study, the higher rainfall recorded during the summer might be the explanation for the higher biomass and diversity observed in the studied streams.…”
Section: Discussionsupporting
confidence: 59%
“…Water age should be more important for zooplankton than for phytoplankton due to the longer generation time of zooplankton (BASU and PICK, 1997). On the other hand, in a survey on the Po River (Italy) ROSETTI et al (2009) found significant influences of temperature and trophic conditions, but no direct effects of the hydrological regime on zooplankton. However, the Po River is confined within artificial banks, which results in poor connection between the main arm and its floodplain.…”
Section: Introductionmentioning
confidence: 96%
“…In regulated rivers, the altered hydrology affects solid transport and sedimentation rates and can amplify the effects of nutrient loadings, inducing eutrophication processes (Dodds 2006;Hilton et al 2006;Rossetti et al 2008). Current velocity and water turbulence have also been recognized as prime factors regulating growth and distribution of submerged macrophytes (Madsen et al 2001;Sand-Jensen 2008).…”
Section: Introductionmentioning
confidence: 99%